Normalizing Rejection. (February 2016) - Conn, Vicki S.; Zerwic, Julie; Jefferson, Urmeka; Anderson, Cindy M.; Killion, Cheryl M.; Smith, Carol E.; Cohen, Marlene Z.; Fahrenwald, Nancy L.; Herrick, Linda; Topp, Robert; Benefield, Lazelle E.; Loya, Julio
Getting turned down for grant funding or having a manuscript rejected is an uncomfortable but not unusual occurrence during the course of a nurse researcher's professional life. Rejection can evoke an emotional response akin to the grieving process that can slow or even undermine productivity. Only by "normalizing" rejection, that is, by accepting it as an integral part of the scientific process, can researchers more quickly overcome negative emotions and instead use rejection to refine and advance their scientific programs. This article provides practical advice for coming to emotional terms with rejection and delineates methods for working constructively to address reviewer comments.